Development Of Smartphone Application To Improve Facility Management System In Johor Bahru Sentral - Aji, Azman Hafiidz (2019)
Facility management is an integrated systematic approach of operation, maintenance and security of a facility. It is designed to meet the demand and supply of the facility to ensure functionality, comfort and safety of the people within the facility. An efficient facility management focused to encompass many aspects includes high performance, efficient service deliveries and high-end security. The most challenging part to sustain a facility is to meet the user’s requirements and satisfaction. Lacking of information’s given by the user’s complaints have been the main issue for an organization to delivers high performance. This issue is investigated in this study and later proposed a counter measure for such improvement. To that matter, this study intends to determine factors that influence efficiency in Facility Management services and investigate the cause of current deficiencies that rise in the organization. Upon completion of the determination, an application is developed based users requirement is proposed. The adopted methodology to achieve the first two objectives is based on a survey study. Results revealed that the respondents have a mutual agreement that the effectiveness of facility management services mostly influenced by their understanding in the job description and clarification. Three main factors that affect the respond time to rectify the complaint made by complainer is mainly due to the; incomplete complaint information, lacking in the complaint record and incomplete complainer personal details for further conversations. Proceeds, an application based complaint system, Appdolf configured several users that include consumers or complainers, technical personnel’s and other managerial personnel’s is developed. The features in the application are developed based end-user requirements and ensuring accurate and precise information’s are generated for further process in repairing and rectifications by the technical personnel’s. To this reason, barriers that have been investigated previously such as incomplete information’s can be reduced and further eliminated while offering better performance and increase facility management services to meet the end-user requirements, specifically at JB Sentral Building. To this way, an effective and efficient of service deliveries to the stakeholders of JB Sentral Building can be achieved while promoting a high-end performance of facility management.